Extraordinary optical transmission and enhanced magneto-optical effects induced by hybrid waveguide-surface plasmon polariton mode in bilayer metallic grating. (20th February 2017) - Lei, Chengxin; Wang, Sihao; Tang, Zhixiong; Li, Daoyong; Chen, Leyi; Tang, Shaolong; Du, Youwei
Abstract: We predict theoretically a significant enhancement of the magneto-optical Faraday rotation and extraordinary optical transmission in the bilayer metallic grating. Calculations, based on the extended finite difference time domain method, demonstrate that in such structures the Faraday rotation spectrum has several resonant peaks in a broad spectrum spanning visible to near-infrared frequencies, some of them coinciding with transmittance peaks, providing simultaneously an up to 44-fold Faraday rotation enhancement and high transmittance of 57%, which is quite favorable for the potential application of novel optical and magneto-optical devices. Meanwhile, two pairs of resonant Faraday rotation angles whose signs are opposite can be achieved in the visible and near-infrared wavelength ranges. It is most important that the wavelength position and amplitude of the transmittance and Faraday rotation can be simply tailored by the incident angle of incident light, the period of the designed system, and so on. We research the implied physical mechanism of the resonance characteristics of transmittance and Faraday rotation by investigating the influences of different incident angles and periods on them and the electromagnetic field distributions at the location of resonance. It is found that the resonant peaks and dips are determined by different hybrid modes of waveguide resonance mode and surface plasmon polariton mode, and the conversion of the TM- and TE-mode in the magnetic dielectric layer mostly governs the enhancement of the Faraday rotation. These research findings will be useful for the design of novel surface plasmon magneto-optical devices in the future.